Tungsten oxide nanowires grown on amorphous-like tungsten films. (17th August 2015) - Dellasega, D; Pietralunga, S M; Pezzoli, A; Russo, V; Nasi, L; Conti, C; Vahid, M J; Tagliaferri, A; Passoni, M
Abstract: Tungsten oxide nanowires have been synthesized by vacuum annealing in the range 500–710 °C from amorphous-like tungsten films, deposited on a Si(100) substrate by pulsed laser deposition (PLD) in the presence of a He background pressure. The oxygen required for the nanowires formation is already adsorbed in the W matrix before annealing, its amount depending on deposition parameters. Nanowire crystalline phase and stoichiometry depend on annealing temperature, ranging from W18 O49 -Magneli phase to monoclinic WO3 . Sufficiently long annealing induces the formation of micrometer-long nanowires, up to 3.6 μ m with an aspect ratio up to 90. Oxide nanowire growth appears to be triggered by the crystallization of the underlying amorphous W film, promoting their synthesis at low temperatures.